Elderly perception on their dietary practices and prophetic foods intake: Preliminary findings - Zainuddin, Norain; Hamirudin, Aliza Haslinda; A. Rahman, Nor Azlina; Sidek, Suriati (Kulliyyah of Allied Health Sciences IIUM Kuantan Campus, Pahang, 2016)
Prophetic (sunnah) foods are gaining an upsurge interest among Muslim community in Malaysia. This is shown by huge number of prophetic food products manufactured by local Muslim companies. This has demonstrated an increased awareness in practicing the Sunnah of Prophet Muhammad S.A.W. No study has examined the perception of Malaysian elderly on prophetic foods intake. Thus, this study aimed to assess elderly perception on their dietary practices, particularly the intake of prophetic foods. Individual in-depth semi-structured interviews were conducted with six elderly aged 60 years and older living in three FELDA in Terengganu. The interview covered the participants’ daily dietary practices and intake as well as knowledge and belief on the benefit of consuming prophetic foods. Interviews were audiorecorded, and transcribed verbatim. Participants believed that ageing was associated with a reduced dietary intake due to loss of appetite. Elderly consumed a supplement because they considered their daily dietary intake is insufficient as well as to improve their health problems. They preferred the prophetic food products as they perceived that the products intake as a practice of Prophet Muhammad S.A.W. In conclusion, the elderly believed that intake of prophetic food could improve their health and nutritional status.